2001
DOI: 10.1007/bf03401854
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Heme-Oxygenase-1: Expression, Regulation, and Possible Functions in Skin Repair

Abstract: The observed injury-mediated increase in HO-1 mRNA and protein at the wound site was due to infiltrating HO-1 expressing monocytic cells. Macrophage-derived HO-1 expression was not under regulatory control by NO in skin repair. We provide evidence that HO-1 might exert a regulatory role in macrophage-derived cytokine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 63 publications
3
27
0
1
Order By: Relevance
“…We therefore suspected that the HO-1 in this study was derived from macrophages. This result is consistent with a report on the skin wound repair process in mice [40], and also with a previous report on HO expression in macrophages [34].…”
Section: Discussionsupporting
confidence: 95%
“…We therefore suspected that the HO-1 in this study was derived from macrophages. This result is consistent with a report on the skin wound repair process in mice [40], and also with a previous report on HO expression in macrophages [34].…”
Section: Discussionsupporting
confidence: 95%
“…In excisional wounds and psoriatic skin, HMOX1 mRNA, and protein were observed to be increased in the hyperproliferative epidermis and infiltrating macrophages [30,32,33]. Moreover, various models of inflammation have demonstrated that pharmacological modulation of HMOX1 expression can have a positive impact on the cutaneous wound healing process.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, by infiltrating, these cells import the HO system into the wounded area and cause protection via the immediate generation of the antiinflammatory and antioxidative heme metabolites biliverdin/ bilirubin and CO, and the up-regulation of ferritin. 50 When HO activity is inhibited by pharmacologic agents such as SnMP, administration of heme aggravated influx of granulocytes and macrophages as compared with heme treatment alone. HO activity may, via the generation of antioxidants biliverdin/bilirubin and vasodilator CO, function as a feedback mechanism by downregulating adhesion molecules and thereby alleviating recruitment of immune cells and the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is present mainly near the basal membrane in proliferating keratinocytes. 50 HO-2, the HO isoform that is able to bind heme, may therefore function as a first scavenger against heme-induced insults, whereas HO-1, present in the first layers of the epidermis and in infiltrating leukocytes, degrades heme to generate its potent cytoprotective breakdown products. Therefore, HO seems to form a general protective layer to withstand the continuous oxidative and mechanical insults of which the skin daily suffers.…”
Section: Discussionmentioning
confidence: 99%